Four α-particle decay of the excited 16O* quasi-projectile in the 16O + 12C reaction at 130 MeV. (22nd October 2019) - Bruno, M; D'Agostino, M; Managlia, M V; Morelli, L; Baiocco, G; Gulminelli, F; Frosin, C; Barlini, S; Buccola, A; Camaiani, A; Casini, G; Cicerchia, M; et al.
Abstract: The four α -particle decay of the excited 16 O* quasi-projectile (QP) produced in peripheral 16 O +  12 C reactions at 130 MeV is studied in detail. The different decay channels leading to the four α -particle final state are reconstructed from an event-by-event analysis of α correlations through the population of intermediate 8 Be and 12 C resonant states. A small but non-negligible contribution of 8 Be gs evaporation is observed. The branching ratios of the different evaporation channels are compared to the prediction of an Hauser-Feshbach code (once characteristics of the QP source are extracted from the experimental data), which very accurately reproduces all the inclusive observables of the reaction. However, significative deviations are observed. In particular, the experimental population of the Hoyle state is significantly lower than the predictions of the statistical model, suggesting possible structure effects in the Coulomb barrier and/or in the transmission coefficients.